Examining faculty priorities: making connections across coursework - Rupnow, Rachel; Hill, Alexandra (Research in mathematics education, 2025)
Mathematics is central to STEM coursework, yet limited research has examined how instructors in mathematics and other STEM courses facilitate connections between courses for their students at the university level. Based on pre-surveys and focus group meetings with faculty members across departments, we describe factors that participants characterised as assisting or hindering making connections between courses. We further examine these characteristics' relationship to participants' pedagogical content knowledge and beliefs. Results include the positive impact of personal relationships with other faculty for enhancing connections as well as the largely negative impact of knowledge and beliefs about the university context on faculty's willingness and ability to make connections. Implications include the need to examine and consider the impact of institutional policies before creating interventions for facilitating connections across contexts.